Artists' roles and digital strategies in the 2024 Indonesian presidential election - Subekti, Dimas; Hapsa, Hapsa; Rohayati, Wahyu (Jurnal Studi Komunikasi, 2025)
This research explains the roles and strategies of influencer artists who collaborate with presidential and vice-presidential candidate pairs in conducting political campaigns through digital media in the 2024 general elections. This research uses a qualitative method with a case study approach. The data collection technique in this research is a literature study. The finding of this research is that influencer artists supporting Prabowo Subianto-Gibran Rakabuming Raka are dominant in taking on the icon role in their digital political campaigns. Meanwhile, influencer artists supporting Anies Baswedan-Muhaimin Iskandar and Ganjar Pranowo-Mahfud MD are more predominant in the role of messengers. Furthermore, in their digital political campaign strategies, these influencer artists use ways to create creative content, mobilise fanbases incorporated in their social media, conduct giveaways and carry out live streaming routines on their respective digital platforms and other people's channels. Therefore, this study explains that the power of digital media, coupled with a recognised figure in the channel, significantly impacts electoral politics if utilised in a directed and measured manner.